Characterization and photocatalysis of alumina bead supported Fe3+ doped TiO2 photocatalyst - Bajamundi Cyril Jose E. (2010)
Ferric ion was introduced to titania-P25 (Degussa) by ultrasonic wer impregnation technique. The concentration of the dopant was varied from 0.0 at % Fe/Ti ratio. The doped titania was then loaded to alumina balls using mechanical coating technique and followed by calcination in air at 300, 400, 450 and 550°C. The fabricated photocatalysts was characterized by X-Ray diffraction, specific surface area, scanning electron microscopy, UV-Vis diffuse reflectance spectroscopy, photoluminescence spectroscopy, zeta potential measurement and X-ray absorption near-edge spectrum (XANES). The photocatalytic activity of the catalysts was evaluated by tracking degradation of the probe-organic - Methylene Blue under UV light. The catalysts with 0.1 at % Fe3+ concentration calcined at 400 °C gave the highest photocatalytic performance of up to 98% degradation of the probe organic. The effect of process parameters: intial pH (3,7,9), initial MB concentration (10, 20, 30 mg/L) and UV light source (10, 18, 36 W) was examined. pH =7 is best for the degradation of MB due to surface charge and adsorbate compatibility considerations. The initial MB concentration of 20 mg/L is the optimum initial concentration because it balances the need for high rates and photocatalyst shielding. The initial degradation rate and the final % degradation increases with the UV light source power. In addition the degradation kinetics was modeled using Langmuir-Hinshelwood and pseudo-first order model.
"April 2010."
Thesis (M.S. Chemical Engineering)--University of the Philippines Diliman.
Keywords: Alumina bead